Avtoimunost - mehanizmi in pomen redoks procesov - Omersel, Jasna (Farmacevtski vestnik, 2010)
The collapse of the self-tolerance mechanisms leads to the development of autoimmunity and the onset of various autoimmune diseases. Currently the attention to find the reasons for the observed altered immunoreactivity of thelymphocytes and antigens is focused not only on the known genetic and immunological factors, fluctuations in the hormone state and environmental triggers, but also directly on the antibody structure. It was proposed that the alteration in their basic structure can also occur due to the oxidative environment in and outside of the body. Such oxidation changes in constant andvariable regions can modify three-dimensional structure of antibodies, affecting their effector functions and altering their binding affinity towardsbody s own-proteins.
Keywords: avtoimunost; oksidacija; protitelesa; redoks potencial